2005
DOI: 10.1143/jjap.44.7883
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Rotating-Disk Chemical Vapor Deposition Process for In-Situ Arsenic-Doped Polycrystalline Silicon Films

Abstract: We have developed high-speed rotating-disk chemical vapor deposition (CVD) equipment for polycrystalline silicon (poly-Si) films. This CVD equipment has an enhanced ability to reduce the boundary layer thickness at a given temperature above a wafer surface, and to suppress vapor-phase reactions. We investigated in-situ arsenic-doped poly-Si film deposition using silane (SiH4), arsine (AsH3) and nitrogen (N2) in a high-speed rotating-disk CVD as functions of AsH3 flow rate and deposition temperature. Both the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…b, two peaks spaced by 180° were observed for both ZnO and sapphire, since the crystal lattices of m‐plane ZnO and m‐plane sapphire are both rectangular with two‐fold symmetry. The c ‐axes of ZnO and that of sapphire perpendicularly crossed each other on the sapphire substrate, namely ZnO [0001] || sapphire and ZnO || sapphire [0001]. In this φ scan measurement, the ZnO (10–11) and sapphire (11–20) planes were used as the monitoring planes, where Bragg conditions were set to be satisfied.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…b, two peaks spaced by 180° were observed for both ZnO and sapphire, since the crystal lattices of m‐plane ZnO and m‐plane sapphire are both rectangular with two‐fold symmetry. The c ‐axes of ZnO and that of sapphire perpendicularly crossed each other on the sapphire substrate, namely ZnO [0001] || sapphire and ZnO || sapphire [0001]. In this φ scan measurement, the ZnO (10–11) and sapphire (11–20) planes were used as the monitoring planes, where Bragg conditions were set to be satisfied.…”
Section: Resultsmentioning
confidence: 99%
“…and , it was shown that the thickness and crystallographic properties were homogeneous across the substrate, and that the ZnO film was epitaxially grown on the sapphire substrate . In the direction lateral to the sapphire substrate, four small rectangular ZnO lattices are formed on one large sapphire rectangular lattice in the sapphire [0001] direction, indicating domain‐matching epitaxy , where the lattice mismatch in the ZnO [0001] direction is 9.7%, and that in the ZnO direction is 0.1%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations